Analisis Efektifitas Halte Di Kota Medan - SITOHANG, Oloan; SITUMORANG, Anto Ervin (Fakultas Teknik Universitas Katolik Santo Thomas, 2019)
In the city of Medan, bus shelter where passengers could wait for Angkot (local paratransit) to stop has not been fully utilized. In this study, we evaluate the effectiveness of bus shelters along main corridor in Medan. The evaluation is conducted based on official government standard, occupancy level, and also user perception. We have surveyed 35 shelters, among which 16 stops (45.71%) are mid-block, 8 stops (22.86%) are farside, and 11 types (31.43%) are near-side. In accordance with bus stop standards, only 9 stops (25.71%) are considered . The results of this study indicate that the factors that influence the use of shelters in waiting for Angkot are as follows: awareness about shelters location, distance to reach shelters, waiting times at shelters, shelter facilities. The effectiveness of using bus stops in Medan City is 32.58%, which means the shelter in this corridor is considered veryineffective (between 20.10% -40.00%).